1996
DOI: 10.1111/j.1476-5381.1996.tb16724.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tedisamil (KC‐8857) on cardiac electrophysiology and ventricular fibrillation in the rabbit isolated heart

Abstract: 1 The direct cardiac electrophysiological and antifibrillatory actions of tedisamil (KC-8857) were studied in rabbit isolated hearts.2 Tedisamil (1, 3, and 10 gM), prolonged the ventricular effective refractory period (VRP) from 120±18 ms (baseline) to 155 + 19, 171+20, and 205+14 ms, respectively. Three groups of isolated hearts (n = 6 each) were used to test the antifibrillatory action of tedisamil. Hearts were perfused with 1.25 Mm pinacidil, a KATP channel activator. Hearts were subjected to hypoxia for 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…Tedisamil was obtained from Kali‐Chemi (Hanover, Germany) and dofetilide was obtained from Pfizer (Sandwich, U.K.). The test concentrations of tedisamil were selected on the basis of previous studies in our laboratory ( Chi et al ., 1996 ; Friedrichs et al ., 1998 ), as well as others ( Tsuchihashi & Curtis, 1991 ), which demonstrated that tedisamil had antiarrhythmic actions over this concentration range (0.3 – 3 μ M ) in vitro and in vivo . The lowest concentration of dofetilide (3 n M ) was selected on the basis of a literature report that demonstrated the antiarrhythmic activity of this drug in man ( Echt et al ., 1995 ).…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Tedisamil was obtained from Kali‐Chemi (Hanover, Germany) and dofetilide was obtained from Pfizer (Sandwich, U.K.). The test concentrations of tedisamil were selected on the basis of previous studies in our laboratory ( Chi et al ., 1996 ; Friedrichs et al ., 1998 ), as well as others ( Tsuchihashi & Curtis, 1991 ), which demonstrated that tedisamil had antiarrhythmic actions over this concentration range (0.3 – 3 μ M ) in vitro and in vivo . The lowest concentration of dofetilide (3 n M ) was selected on the basis of a literature report that demonstrated the antiarrhythmic activity of this drug in man ( Echt et al ., 1995 ).…”
Section: Methodssupporting
confidence: 62%
“…Tedisamil is an experimental bradycardic agent being developed for the treatment of angina pectoris ( Fox et al ., 2000 ). The drug prolongs cardiac action potentials and the QT interval of the ECG in experimental animals ( Beatch et al ., 1991 ; Tsuchihashi & Curtis, 1991 ; Rees et al ., 1993 ; Wallace et al ., 1995 ; Chi et al ., 1996 ) and in man ( Bargheer et al ., 1994 ; Fox et al ., 2000 ). Tedisamil brings about these effects via blockade of several cardiac ion currents.…”
Section: Introductionmentioning
confidence: 99%
“…Tedisamil has been described as an antiarrhythmic drug (Chi et al 1996), which in rat ventricular myocytes provokes marked prolongation of action potentials (Dukes and Morad 1989). This effect was explained by a selective inhibition of fast inactivating transient outward current (Dukes and Morad 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Die leichte Verlängerung der QT-und QT c -Dauer nach Gabe von Tedisamil als Indikator für eine verlängerte ventrikuläre Repolarisationsphase könnte einen antiarrhythmischen Effekt bewirken, wie dies bereits in tierexperimentellen Untersuchungen gezeigt werden konnte (1,2,4,6,11,31). Die Supprimierung von ischämiebedingten Arrhythmien, was nicht Gegenstand der vorliegenden Arbeit war, beruht bei Tedisamil primär wahrscheinlich auf der Wirkung auf ATPabhängige Kaliumkanäle.…”
Section: Diskussionunclassified
“…Tedisamildihydrochlorid ist eine neuartige bradykardisierende Substanz mit nachweisbaren antiischämischen (7,14) und antiarrhythmischen Eigenschaften (1,2,4,6,11,31). Tedisamil führte nachweislich zur Inhibierung verschiedener repolarisierender (8,9,10) sowie zahlreicher neuronaler (9,10,21) und vaskulärer (17,22,23) K + -Kanäle.…”
Section: Introductionunclassified